2015
DOI: 10.1007/s00382-015-2918-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential for seasonal prediction of Atlantic sea surface temperatures using the RAPID array at 26 $$^{\circ }$$ ∘ N

Abstract: found that at a 5-month lag, the Ekman component mainly contributes to the southern part of the dipole and cumulative air-sea fluxes only explain a small fraction of the SSTA variability. Given that the southern part of the SSTA dipole encompasses the main development region for Atlantic hurricanes, our results therefore suggest the potential for AMOC observations from 26 • N to be used to complement existing seasonal hurricane forecasts in the Atlantic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 69 publications
4
33
0
Order By: Relevance
“…The most important shortcoming of this approach is the necessity of long and widespread observations from hardly accessible regions like the deep ocean. The third method relies on the identification of significant statistical relationships between the AMOC and other oceanic and atmospheric variables, such as the sea surface temperature and height (Latif et al 2004;Zhang 2008;Willis 2010;Duchez et al 2016), the deep Labrador sea water densities (Robson et al 2014), or the cumulative effect of heat fluxes in the deep convection regions (Ortega et al 2011). However, these covariances have been mostly established using models, which have inevitable biases that may compromise the reality of these inferred relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important shortcoming of this approach is the necessity of long and widespread observations from hardly accessible regions like the deep ocean. The third method relies on the identification of significant statistical relationships between the AMOC and other oceanic and atmospheric variables, such as the sea surface temperature and height (Latif et al 2004;Zhang 2008;Willis 2010;Duchez et al 2016), the deep Labrador sea water densities (Robson et al 2014), or the cumulative effect of heat fluxes in the deep convection regions (Ortega et al 2011). However, these covariances have been mostly established using models, which have inevitable biases that may compromise the reality of these inferred relationships.…”
Section: Introductionmentioning
confidence: 99%
“…However, these covariances have been mostly established using models, which have inevitable biases that may compromise the reality of these inferred relationships. Besides, direct observations of the AMOC are still too short and can only be used to identify significant relationships at the monthly timescale (Duchez et al 2016), which do not necessarily hold at decadal and longer timescales. Finally, climate models can also be used to constrain the past AMOC evolution, by assimilating the observed variability of relevant climate quantities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…
It has been suggested that changes in the Atlantic Meridional Overturning Circulation (AMOC) can drive sea surface temperature (SST) on monthly time scales (Duchez et al, 2016, https://doi.org/ 10.1007/s00382-015-2918-1). However, with only 11 years of continuous observations, the validity of this result over longer, or different, time periods is uncertain.
…”
mentioning
confidence: 99%
“…Based on the observations thus far, telemetry of data from these two moorings would accurately estimate of interannual variability including the large downturn in 2009/2010. Near real‐time AMOC data could thus aid the prediction of seasonal climate patterns [ Duchez et al ., ] and extreme sea level rise events [ Goddard et al ., ] and would provide a valuable estimate of the subclimate time scale AMOC variability.…”
Section: Discussionmentioning
confidence: 99%
“…The correct initialization of these SST patterns was crucial to the successful seasonal forecast of that year's negative NAO [Maidens et al, 2013]. Duchez et al [2015] show that AMOC variations precede certain SST patterns and could thus feed into the predictions of these SSTs and improved seasonal forecasts, if near real-time AMOC estimates were available. Regarding the latter, following the dip in the AMOC in 2009/2010, sea level in New York rose by 10 cm 2 months later [Goddard et al, 2015].…”
Section: Introductionmentioning
confidence: 99%